Understanding the facet-dependent catalytic performance of hematite microcrystals in a CO oxidation reaction. Issue 9 (10th August 2018) - Sun, Liming; Zhan, Wenwen; Li, Yan-An; Wang, Fan; Zhang, Xueliang; Han, Xiguang
Abstract : α-Fe2 O3 microcrystals with uniform plate, cube and rod morphologies have been synthesized. DFT calculations and experimental results indicated that the Fe2 O3 nanorods showed an obvious improvement of CO catalytic activities due to their unique surface structure. Abstract : Hematite (α-Fe2 O3 ) with well-defined plate, cube and rod morphologies has been successfully synthesized, which predominantly exposes the (001), (012) and (110) facets, respectively. Rod-like α-Fe2 O3 with exposed (110) facets showed a greater CO catalytic activity than catalysts with all other morphologies. X-ray photoelectron spectroscopy (XPS) results and theoretical calculation analysis revealed that the different catalytic activities over the catalysts with various morphologies could be attributed to various catalytic mechanisms caused by different surface structures, leading to different activation energies in CO oxidation catalysis by α-Fe2 O3 (001), (012) and (110) facets.